Use of biofermented plants adapted to the semi-arid region in piglet diets - Oliveira, Elton Roger Alves De; Martins, Terezinha Domiciano; Thomaz, Maria Cristina [UNESP]; Pascoal, Leonardo Augusto Fonseca; Silva, José Humberto Vilar Da; Silva, Taisa Rocha Gomes Da; Brito, Mariany De Souza; Almeida, Jonathan Mádson Dos Santos; Almeida, Jorge Luiz Santos De (UFBA - Universidade Federal da Bahia, 2021)
Two experimental tests were carried out to evaluate the inclusion of a biofermented semi-arid plant mix in diets of piglets in the initial weaning phase. In the first trial, the nutritional value and digestibility of nutrients and the digestible and metabolizable energy values ​​of the bio-fermented plants mix were evaluated. To do so, eight piglets with an initial average weight of 15.2 ± 2.7 kg were used, housed in metabolic cages, and using the total collection of feces and urine. The bio-fermented plant mix diet presented 80.40% and 68.18% as digestibility coefficients for dry matter and crude fiber, respectively; 10.08% crude protein and 2,865 kcal/kg of metabolizable energy. In the second trial, the inclusion of 0, 3, 6 and 9% of bio-fermented plant mix was evaluated on performance, diarrhea incidence, plasma components, weight, and length of digestive organs of piglets in the initial weaning phase. To do so, 40 piglets with an initial average weight of 12.6 ± 3.5 kg were used, distributed in a randomized block design with four treatments, five replicates, and two animals per experimental unit. The inclusion of different levels of bio-fermented plant mix did not affect (P>0.05) the performance, weight, and length of digestive organs or serum parameters. However, the inclusion of bio-fermented plant reduced (P<0.01) the diarrhea incidence. It is concluded that bio-fermented plants adapted to the semi-arid region has the potential to be used in diets for pigs in the initial weaning phase.

Foram realizados dois ensaios experimentais para avaliar a inclusão de biofermentado a base de plantas do semiárido na dieta de leitões na fase inicial. No ensaio I foi avaliado o valor nutricional e a digestibilidade dos nutrientes e os valores de energia digestível e metabolizável do biofermentado. Para tanto, foram utilizados oito leitões com peso médio inicial de 15,2 ± 2,7 kg, alojados em gaiolas de metabolismo, utilizou-se o método de coleta total de fezes e urina. O biofermentado apresentou 80,40% e 68,18% como coeficientes de digestibilidade para a matéria seca e fibra bruta, respectivamente; 10,08% de proteína bruta e 2.865 kcal/kg de energia metabolizável. No segundo ensaio foi avaliada a inclusão de 0; 3; 6 e 9% de biofermentado sobre o desempenho, incidência de diarreia, componentes plasmáticos, peso e comprimento de órgãos digestivos de leitões na fase inicial. Para tanto, foram utilizados 40 leitões com peso médio inicial de 12,6±3,5 kg, distribuídos em delineamento em blocos casualizados com quatro tratamentos, cinco repetições e dois animais por unidade experimental. A inclusão dos diferentes níveis de biofermentado não afetou (P>0,05) o desempenho, o peso e comprimento dos órgãos digestivos e parâmetros séricos. No entanto, a inclusão do biofermentado reduziu (P<0,01) a incidência de diarreia. Conclui-se que o biofermentado a base de plantas adaptadas ao semiárido apresenta potencial de ser utilizado em dietas para suínos na fase inicial.
Uso de biofermentado de plantas adaptadas ao semiárido na dieta de leitões
Keywords: Unconventional feeds; performance; digestibility; fermentation; swine; alimentos não convencionais; desempenho; digestibilidade; fermentação; suíno